The lipoprotein HP1454 of Helicobacter pylori regulates T‐cell response by shaping T‐cell receptor signalling. (31st January 2019) - Capitani, Nagaja; Codolo, Gaia; Vallese, Francesca; Minervini, Giovanni; Grassi, Alessia; Cianchi, Fabio; Troilo, Arianna; Fischer, Wolfgang; Zanotti, Giuseppe; Baldari, Cosima T.; de Bernard, Marina; D'Elios, Mario M.
Abstract: Helicobacter pylori (HP) is a Gram‐negative bacterium that chronically infects the stomach of more than 50% of human population and represents a major cause of gastric cancer, gastric lymphoma, gastric autoimmunity, and peptic ulcer. It still remains to be elucidated, which HP virulence factors are important in the development of gastric disorders. Here, we analysed the role of the HP protein HP1454 in the host–pathogen interaction. We found that a significant proportion of T cells isolated from HP patients with chronic gastritis and gastric adenocarcinoma proliferated in response to HP1454. Moreover, we demonstrated in vivo that HP1454 protein drives Th1/Th17 inflammatory responses. We further analysed the in vitro response of human T cells exposed either to an HP wild‐type strain or to a strain with a deletion of the hp1454 gene, and we revealed that HP1454 triggers the T‐cell antigen receptor‐dependent signalling and lymphocyte proliferation, as well as the CXCL12‐dependent cell adhesion and migration. Our study findings prove that HP1454 is a crucial bacterial factor that exerts its proinflammatory activity by directly modulating the T‐cell response. The relevance of these results can be appreciated by considering that compelling evidence suggest that chronic gastric inflammation, a condition that paves the way to HP‐associated diseases, is dependent on T cells.